Undergraduate dermatology education in Portugal: Current status and future directions - Catarina Queirós; Luís Soares- (Sociedade Portuguesa de Dermatologia e Venereologia, 2022)
Introduction: Although dermatologists represent a small proportion of medical doctors in Portugal, dermatological problems are very common, particularly in primary health-care settings. Therefore, an adequate training in dermatology is essential, even for medical students who will later follow other specialties. Objectives: The aim of the study was to analyze the state of the art of undergraduate dermatology teaching in Portugal. Methods: An electronic survey was applied to the heads of the various medicine schools. Questions were directed, among other topics, toward hours of teaching, number of teachers and students, teaching and assessment methods, curriculum, and competencies covered. Results: The eight Portuguese medical schools responded to the survey. The number of hours of dermatology teaching across medical schools ranged from 14 h to 60 h. Teaching methods varied widely between schools, encompassing lectures, tutorials or small group learning, and clinical exposure, among others. Regarding the content of lectures, which remain the primary method of teaching, all schools include skin cancer in their curriculum. The next topics more frequently covered are eczema and cutaneous infections. All medical schools are currently assessing competency in dermatology, multiple-choice questions being used by all schools. Conclusions: Although some improvements have been achieved in recent years, undergraduate dermatology training still faces some problems, namely, the lack of teachers, the excessive number of students, and an insufficient resource allocation by medical school directors. To improve dermatology education in Portugal, one of the most important points would be the establishment of a pre-defined curriculum that could serve as a basis for the various medical schools. Distribution of teaching contents throughout pre-clerkship and clerkship years and access to digital platforms with selected resources would be additional forms of improving and standardizing dermatology education, to equip future doctors with the necessary skills to diagnose and manage common dermatological conditions.